The Spatiotemporal Dynamics of the Landscape of the Itombwe Nature Reserve and Its Periphery in South Kivu, the Democratic Republic of Congo - Cléophace Bayumbasire Citwara; Trésor Mbavumoja Selemani; Julien Bwazani Balandi; Nadège Cizungu Cirezi; André Nduwimana; Léonard Mubalama Kakira; Kouagou Raoul Sambieni; Jean-Pierre Mate Mweru; Jean-François Bastin; Hervé Tchekote; Jan Bogaert (Land)
This study examines the evolution of anthropogenic pressures on the Itombwe Nature Reserve and its periphery over the period 1990–2024 using satellite imagery. Two landscape ecology indices were employed: the Percentage of Landscape (PLAND) and the Largest Patch Index (LPI). The PLAND quantifies the overall extent of each habitat type, while the LPI provides insights into their spatial configuration. Eighty-three plots (each 2.5 km per side, i.e., 6.25 km2) were sampled in both the reserve and its periphery to generate robust landscape replications. Analysis focused on three key land use classes: forests, savannahs, and fields. Statistical comparisons using Kruskal–Wallis and Mann-Whitney U tests revealed a decline in forest cover within the reserve and its periphery, accompanied by a steady increase in savannahs and fields. The decline in forest cover is particularly pronounced along the reserve’s periphery. For instance, in the reserve, forest cover decreased from 78.4% in 1990 to approximately 60.2% in 2024, whereas on the periphery, it dropped from 37.5% to about 21.4%. In contrast, the savannah areas increased from 17.7% to 29.5% within the reserve and maintained a marked predominance on the periphery (rising from 53.9% to 55.2%). Additionally, the area dedicated to fields exhibited notable expansion, rising from 3.70% to 10.22% in the reserve and from 7.54% to 21.98% along the periphery. These findings underscore the significant impacts of anthropogenic pressure on the forest ecosystems in both the reserve and its periphery. They highlight the urgent need for enhanced conservation measures within the reserve, as well as the implementation of sustainable land use practices (e.g., agroforestry and sustainable agriculture) in the peripheral zones to reduce the local population’s dependence on forest resources.